THE INFLUENCE OF SHELL FISH FLOUR ON COMMERCIAL RATIONS ON THE CARCASS PERCENTAGE OF ISA BROWN CHICKEN AGE 105 WEEKS - I P. P., Adiantara,; Dewi, G.A.M.K; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 8 No 2 (2020): Vol. 8 No. 2 Tahun 2020; Mei - Agustus, 2020)
This study aims to determine the effect of shellfish flour meal on commercial rations on the percentage of Isa Brown chicken carcasses aged 105 weeks. The design used in this study was a completely randomized design (CRD) with four treatments per treatment using 5 replications and each test using 3 Isa Brown chickens. The four treatments were A commercial ration without clamshell flour, B commercial ration and 1% clamshell flour, C commercial ration and 2% clamshell flour, commercial D ration and 3% clamshell flour. The variables observed in this study included cutting weight, carcass weight, carcass percentage, chest percentage, wing percentage, thigh percentage and back percentage. The results showed that the percentage of thighs in treatments B and D was significantly (P<0.05) higher than that of treatments A and C. Based on the results of this study it was concluded that the administration of clamshell flour at the level of 1% and 3% in commercial rations can increase the percentage of thighs, but can not increase the weight of the cut, carcass weight, carcass percentage, breast percentage, wing percentage and the percentage of chicken back Isa Brown aged 105 weeks.   Keywords : shell fish flour, carcass percentage, isa brown chicken